THE INFLUENCE OF TRUST AND PERCEPTION OF EASY PURCHASING DECISIONS ON THE TIKTOK SHOP APPLICATION (STUDY ON TIKTOK SOCIAL MEDIA USERS IN SURABAYA) - Khalid, Idham; Purwanto, Sugeng (Yayasan Education and Social Center, 2023)
The title of this study is “The Influence of Trust and Perceived Ease of Use on Purchase Decisions in the TikTok Shop Application (A Study on TikTok Social Media Users in Surabaya)”, which aims to determine the influence of trust and perceived Ease of use on purchase decisions. The research method is quantitative, with the population being TikTok social media users in Surabaya. The sampling method is non-probability sampling using purposive sampling, which involves sample selection based on specific criteria. The sample consists of respondents who have made purchases on the TikTok Shop application, totalling 104 respondents. The analytical technique used in this research is the Partial Least Square (PLS) method. The results of this study prove that (1) Trust has a positive and significant influence on Purchase Decisions. (2) Perceived Ease of use positively influences Purchase Decisions